The max muscle plan - Schoenfeld, Brad (Human Kinetics, 2013)
Widely regarded as one of America's leading strength and fitness professionals, the author has won numerous natural bodybuilding titles and has been published or featured in virtually every major fitness magazine. In this book, he brings his expertise to everything needed for completing a total-body transformation in just six months.